EVALUASI TERHADAP PERENCANAAN GEOMETRIK PADA JALAN ALTERNATIF WADUK DARMA KABUPATEN KUNINGAN JAWA BARAT - Fahlifie, Aprizal; Sukirman, Silvia; Haris, Samuan (Jurnal Teknik Sipil ITENAS, 2007)
Highway geometric design is a part of highway planning which focused on physical form planning, so it can fulfil the highway basic function. Highway geometric design consists of horizontal alignment and vertical alignment and each of them has its own calculation. The alternative roads of Kuningan regency is one of important basic infrastructures as an effort to increase social standard of life style among the cities in that area. In addition to those purpose the link that can guarantee our security, comport, fluency, and safety, to its consumer. The location chosen is limited, its only 640, 026 m length. It started from STA 0+000, and ended at STA 0+640,026, West Java Province. The evaluation of this geometric design is based on secondary data obtain from PT INDEC & Associates Limited, as a Consultant Designer of alternative road of Kuningan regency link construction project. From result ofa evaluation can be seen that with superelevation>from 4%, âˆ† big existing, is obtained radian radius value which planned is smaller, while curve of Full Circle need big radius, Considering the mentioned hereinafter third the curve form turned into S-C-S at PI1, PI2, and PI3. By using sloping prices (g,%) of stasioning abscissa and of PPV which have been determined, yielding design planning of vertical alignment which is equal to Consultant planner design.